Immune-related toxic epidermal necrolysis affecting trachea mucosal epithelium: a case report and literature review - Zhang, Mingbo; Fu, Yang; Song, Yuxiao; Gao, Xia; Wang, Jun; Zhang, Bicheng (Frontiers in Pharmacology, 2024)
Background Monoclonal antibodies against programmed cell death protein-1 (PD-1)/programmed death-ligand-1 (PD-L1) have emerged as critical tools in cancer treatment. However, concerns regarding their potential cutaneous and mucosal toxicity, along with severe complications, have drawn clinical attention. Further research is warranted to investigate the adverse reactions and treatment strategies associated with PD-1 monoclonal antibodies. Methods We present a detailed case report of a laryngeal cancer patient who developed toxic epidermal necrolysis (TEN) after treatment with PD-1 monoclonal antibody. We analyzed the etiology, diagnosis, and treatment approaches by integrating clinical manifestations, pathological examinations, and literature research. Results After PD-1 monoclonal antibody therapy, the patient exhibited systemic rash, bullae, and epidermal detachment, which subsequently involved the tracheal and bronchial mucosa, resulting in dyspnea. The patient recovered after treatments with steroids, macrolides, immunoglobulins, and etanercept, along with repeated removal of scabs via bronchoscopy. Literature reviewing suggests a potential association between PD-1 monoclonal antibodies and the pathogenesis of Steven Johnson’s Syndrome (SJS) and Toxic epidermal necrolysis (TEN), possibly due to immune dysregulation. Treatment consists of immediate discontinuation of suspicious drugs, essential supportive therapy, and systemic corticosteroid administration, with the addition of immunosuppressants and/or immunoglobulins needed. Conclusion The mucocutaneous toxicity induced by PD-1 monoclonal antibodies is not limited to the surface of the skin but also in deep mucosal layers, potentially leading to life-threatening complications. Therefore, when using PD-1 monoclonal antibodies, clinicians should closely monitor adverse events and apply appropriate treatments as soon as possible to prevent severe complications.